Association between socio-demographic factors, involvement status in gardening and diet quality among B40 households in Taman Keramat, Kuala Lumpur - Ang, Zheng Feng; Sulaiman, Norhasmah; Balasubramaniam, Baarathi; Mohamed Faidz, Nurakmal Syahirah (Faculty of Medicine and Health Sciences, UPM, 2023)
Introduction: COVID-19 pandemic has impacted the livelihood of Malaysians and gardening activities have contributed positively to the diet quality. This study aimed to determine the factors associated with diet quality among adults in AU2 Keramat, Kuala Lumpur. Methods: The cross-sectional study involved adults aged 18 to 59 via convenience sampling. The socio-demographic, physical activity level and involvement status in gardening were obtained through a questionnaire, while food intake was from a single-day 24-hour diet recall. The diet quality was determined through Malaysian Healthy Eating Index (MHEI) and dietary misreporting was calculated using the Goldberg cut-off method. Results: A total of 117 respondents (65.8 females, 35.2 males) with a mean age of 40.98 were involved in this study. Findings showed that most respondents did not engage in gardening activities (72.6) and the prevalence of poor diet quality in this study was 89.7, with a mean score of 44.51. The older respondents (r= 0.20, p= 0.034) and community gardeners (t= -2.63, p= 0.011) had a significantly higher diet quality but not home gardeners (t= 0.12, p= 0.902). The respondents involved in gardening activity also had a significantly higher fruit serving intake, Mann-Whitney U= 1045.00, p= 0.036) and lower total fat intake (t= 2.27, p= 0.025). Conclusion: The diet quality of the respondents remains poor but community gardeners had significantly higher diet quality and fruit intake while lower total fat intake. Interventions need to be developed to address the persistent poor diet quality of adults in the community.